2014
DOI: 10.1167/iovs.14-15012
|View full text |Cite
|
Sign up to set email alerts
|

Connexin46fs380 Causes Progressive Cataracts

Abstract: Major decreases in connexin levels precede the development of cataracts. These mice represent a useful model for elucidation of the progression of lens abnormalities during cataractogenesis especially as caused by a mutant connexin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 45 publications
(73 reference statements)
2
36
0
Order By: Relevance
“…We have previously shown that Cx46fs380 lenses have decreased gap junctional coupling and develop progressive cataracts (3,28). In this study, we found that expression of Cx46fs380 altered fiber cell homeostasis, causing cell membrane depolarization, decreased activity of epithelial Na ϩ -K ϩ -ATPase, and increased center-to-surface gradients of hydro-static pressure and intracellular concentrations of sodium and calcium ions.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…We have previously shown that Cx46fs380 lenses have decreased gap junctional coupling and develop progressive cataracts (3,28). In this study, we found that expression of Cx46fs380 altered fiber cell homeostasis, causing cell membrane depolarization, decreased activity of epithelial Na ϩ -K ϩ -ATPase, and increased center-to-surface gradients of hydro-static pressure and intracellular concentrations of sodium and calcium ions.…”
Section: Discussionmentioning
confidence: 58%
“…3 in the present study). These differences may reflect the reductions of Cx50 as well as Cx46 in Cx46fs380 lenses (3,28).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations